STUDY OF THE CONNECTIONS OF DIFFERENT LANGUAGES (RUSSIAN AND UZBEK) (British Journal of Global Ecology and Sustainable Development, 2023)
In this article, we explore the relationship between different languages, namely Russian and Uzbek. The methodological approach is based on a comparative analysis of vocabulary, grammar and phonetics. The results of the study showed that the Uzbek language has a large number of borrowings from the Russian language, which is associated with historical factors and modern political and economic ties between the two countries.